The rise and fall of dispensationalism: how the Evangelical battle over the end times shaped a nation - Hummel, Daniel G. (William B. Eerdmans Publishing Company, 2025)
"The history of dispensationalism as an institutional, cultural, and theological force in evangelicalism"--